Deteksi Dini Faktor Risiko Kehamilan Oleh Bidan - April Artinanda; Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
High-risk pregnancies are a major cause of increased maternal and infant morbidity and mortality. Early detection of pregnancy risk factors by midwives is a strategic step in preventing obstetric complications. This study aims to determine the role of midwives in early detection of pregnancy risk factors and the most common risk factors found in pregnant women. The research method used was descriptive research with a quantitative approach. The sample consisted of 60 pregnant women undergoing prenatal checkups in the working area of ​​Community Health Center X. Data were collected through observation sheets and Maternal and Child Health (KIA) records. The results showed that midwives performed effective early detection of pregnancy risk factors. The most frequently identified risk factors included maternal age, anemia, too close pregnancies, and a history of obstetric complications. The study concluded that early detection of pregnancy risk factors by midwives plays a crucial role in preventing pregnancy complications and improving maternal and fetal safety.